Green Transition and the Business Sector in the European Union and Romania - Iordan Marioara; Chilian Mihaela-Nona; Ciurariu Gabriela (Holistica, 2023)
Increasingly obvious over the last two decades, human society and the economies of all the countries in the world faced and continue to face increasingly accelerated, amplified, diverse and divergent economic, social, political and technological trends and developments, among which three so-called megatrends stand out for intensity and persistence: digitization and automation of production, greening of economies and global economic power shifts. Considering such issues, the paper focuses on a brief analysis of how the green transition affects the business sector (enterprises) in the EU countries, with a focus on Romania - an EU member state that registers a relatively low level of penetration of the circular economy. Indicators of the green economy and eco-innovation and referring to the economic dimension of the circular economy, were used for the analysis. The results show that the EU27 economies generally are leaders in most of the aspects concerning the greening of economies and their business sectors, but Romania reveal certain relative delays of the local business sector in moving towards production and business development methods characteristic of the ecological economy.